How to Increase the Accessibility of Newton's Method for Operators With Center-Lipschitz Continuous First Derivative. (17th February 2022) - Ezquerro, J. A.; Hernández-Verón, M. A.; Magreñán, Á. A.
Abstract: As accessibility of Newton's method is very restrictive under a center-Lipschitz condition for the first derivative of the operator involved, we construct a hybrid iterative method to increase the accessibility of the method, where the modified Newton method is used to predict a good starting approximation for Newton's method. A boundary value problem illustrates this study.